O estoque e o fluxo: o problema nacional em Mário de Andrade - Filipe de Freitas Gonçalves (2021)
The purpose of this work is to understand how the nation problem is configured in the last phase of Mario de Andrade’s (1893-1945) work. Starting from the classic views on the relationship between the problem of individuality and sociability in the work of the poet, it is intended to draw attention and highlight in the author’s texts on the question of nationality the moment when he would have elaborated a synthesis of what, at the throughout of most of his work, it was configured as an irreconcilable opposition between individuality and sociability. This synthesis will be perceived in two moments. First, with regard to his conception of national music, which we apprehended, in his last elaboration, from the conception of nacional allegro developed in the set of chronicles posthumously grouped under the name of O Banquete (1945), we show how the elaboration of nation musical form, in the author’s conception, goes through the overcoming of folks forms and the establishment of classical forms not only as an element of artistic, but also of social significance. Second, realizing a similar phenomenon with regard to the final elaboration of his national language project, we show how Mário’s project is elaborated towards the constitutions of an illustrious commoner, the result of a process of social transformation, as well as literary. As result, in addition to looking for synthesis nexuses in the last phase of Mários’s work, we sought to elaborate, from the conceptions of singularity, universality and particularity, a conception of nationality as strangeness, Mário the Andrade’s perception of the problem as such and its overcoming program.